From Language to Discourse : Selected Papers of VII Linguistic Sharing Forum. - Tanto, Camile (Cambridge Scholars Publishing, 2014)
From Language to Discourse contains selected texts from the 6th and 7th Linguistics Sharing Forums, which took place at the Faculty of Social and Human Sciences of Universidade Nova de Lisboa, on 25th November 2011 and 23rd November 2012, respectively. The articles included in this volume present the results of ongoing research in different domains of linguistics, such as phonology, language acquisition, syntax, and terminology. It is important to mention that these papers should be seen as ...